El profesorado frente al uso de las nuevas herramientas tecnológicas en los procesos de enseñanza aprendizajes en la Universidad Técnica de Babahoyo Extensión Quevedo 2019 - Cortez Burgos, Vivianna Aracely (2019)
The internet is currently a service that is considered basic for human beings since we spend all our time online and this is a great contribution today in the processes we perform in our daily lives such as work, in our social life , and more importantly, our student life, since we must be in constant academic growth, having it as a great contribution in the teaching and learning of higher education. The use of the social web today is considered one of the most important technologies since it has been introduced very quickly in the field of documentation, with the emergence of the social web we have at our disposal a number of technological tools that contribute to educational, collaborative activities, to pedagogy and cognitivism, providing students and teachers with the means to devise new services that improve communication. Among these tools that make up the social web we have the social networks, wikis, multimedia content, communities, etc. We will proceed to conduct an investigation of the use of the social web and its contribution to learning in higher education students, applying collaborative activities through the use of Tics